An Essay on Fiscal Federalism - Oates, Wallace E (Journal of Economic Literature, 1999)
This paper is a selective survey of fiscal federalism. It begins with a brief review and some reflections on the traditional theory of fiscal federalism: the assignment of functions to levels of government, the welfare gains from fiscal decentralization, and the use of fiscal instruments. It then explores a series of important topics that are the subject of current research: laboratory federalism, interjurisdictional competition and environmental federalism, the political economy of fiscal federalism, market-preserving federalism, and fiscal decentralization in the developing and transitional economies.